Right to Freedom of Expression and Social Governance: Legitimizing Centrality of Foundational Principles and Ensuring Social Stability - Dr. Mamoona Yasmeen,; Dr. Farhana Mehmood,; Dr M.Asim Iqbal,; Dr. Zuha Qaiser,; Mr. Zia ur Rehman, (Al-Qanṭara, 2022)
Abstract This paper focuses on how the modern westernized thrust of having limitless right to freedom of expression disregard of the theological and social context mars social and economic stability, making social governance a difficult task. The research sets to explore that Sharia-based social governance system expostulates all these limits, duties, rights and responsibilities interpreted in the light of the new social governance with a western supported utilitarian ethical argument posited by Mill, presenting an individualistic framework having moral responsibility of the governance system to protect individual rights and social theological centrality of the social figures with the purpose of theological and social legitimacy to bring stability. This research sets out to prove the superiority of the Sharia-based governance system with the moral value of protecting right to freedom of expression and centrality of the theo-social figures to ensure stability. However, there is yet room for further research into the measurability of instability caused by the free speech targeting current theo-social figures and impacts on the legal injunctions linked to freedom of expression. Keyword: Right to freedom of expression, social governance, legitimacy, centrality of social figures, theological figures, legitimacy tools